Effects of Enterobacter cloacae HG-1 on the Nitrogen-Fixing Community Structure of Wheat Rhizosphere Soil and on Salt Tolerance - Ji, Chao; Liu, Zhaoyang; Hao, Liping; Song, Xin; Wang, Changdong; Liu, Yue; Li, Huying; Li, Chaohui; Gao, Qixiong; Liu, Xunli (Frontiers in Plant Science, 2020)
The present study investigated the physiological and biochemical characteristics of Enterobacter cloacae HG-1 isolated from saline-alkali soil. We further studied the effect of this strain on the salt tolerance of wheat and on the community structure of nitrogen-fixing bacteria in rhizosphere soil. We determined that the investigated strain had high nitrogen fixation activity and produced iron carriers, 1-aminocyclopropane-1-carboxylic acid deaminase, and plant hormones. The metabolites of this strain contained 2,3-butanediol, [R-(R*, R*)], 2-heptanone, and other growth-promoting and antibacterial substances. The strain was also highly salt-tolerant (10% NaCl). After the inoculation of wheat with the HG-1 strain, we recorded increases in root length, plant height, fresh weight, and dry weight of 19.15%, 18.83%, 16.67%, and 17.96%, respectively, compared with uninoculated plants (P < 0.05). Compared with the leaves of uninoculated plants, the proline concentration in the leaves of inoculated plants increased by 12.43% (P < 0.05), the malondialdehyde level decreased by 27.26% (P < 0.05), K+ increased by 20.69%, Ca2+ increased by 57.53% and Na+ decreased by 31.43% (all P<0.05). Furthermore, we detected that inoculation with the HG-1 strain did not affect the species composition of nitrogen-fixing bacteria in wheat rhizosphere soil at the phylum level. However, the average relative abundance of Proteobacteria was significantly increased, whereas the abundance of Verrucomiorobia was significantly decreased compared with uninoculated plants. At the genus level, we detected 32 genera in control samples and 27 genera in inoculated samples, and the species diversity and relative abundance of samples inoculated with the HG-1 strain decreased compared with uninoculated plants. Inoculated samples had lower abundances of Azospirillum, Rhodomicrobium, and Anabaena. Our study demonstrated that the inoculation of wheat with E. cloacae HG-1 could promote the growth of wheat under salt stress and increase salt stress tolerance. The results of this study investigating the interaction among soil, plants, and microorganisms supplement agricultural microbial databases and could provide a reference for the development of microbial-based saline soil improvement programs.